SPORT TOURISM BERKUDA SEBAGAI DAYA TARIK WISATA ALAM SIDOMULYO STABLE DI KECAMATAN UJUNG BATU - Sinurat, Ridwan; Putra, Ardo Yulpiko; Anniza, Aluwis, Alya Nur (Jurnal Porkes, 2025)
This study aims to explore the potential of equestrian sports tourism at Sidomulyo Stable Nature Tourism. The research method used is qualitative with a case study approach. Data collection techniques include participatory observation, in-depth interviews with owners, managers, and tourists, as well as documentation studies as secondary data. The data was analyzed using SWOT analysis. Based on the collected data, although Sidomulyo Stable has had a positive economic and social impact through its unique horse riding tourism concept, and has not caused significant environmental impact thanks to good horse manure management, potential threats to the preservation of protected forests remain prominent if future development does not prioritize the principles of green design. In addition, managers also face operational challenges in the form of horse maintenance costs and professional trainers, while tourists want improved supporting facilities and better safety guidelines, and the community hopes to be more involved in development and training. In conclusion, Sidomulyo Stable Nature Tourism has great potential, provided that there are updates to the attractions.